Empowerment of Monetary Policy on Economic Growth in South Kalimantan in the Perspective of Progressive Islamic Economics - Saputra, Rian; Sandi Alfianur; maharani, dewi (UMBanjarmasin, 2023)
the empowerment of monetary policy can have a significant impact on economic growth especially in South Kalimantan, especially when viewed from the perspective of Islamic economic progress. In Islam, the monetary policy that must be carried out is to follow the principles of Islamic economics or synchronize with Islamic law which prohibits the practice of usury in carrying out every transaction activity such as justice for all parties without any one party being disadvantaged, balance, sustainability and social equality for the community especially in South Kalimantan, sustainable and inclusive economic growth is also an important goal for many countries especially in Indonesia, because this can improve the quality of life and welfare of the community at large. The progressive Islamic perspective recognizes the need for adaptation and progress in the current global economic context. While sticking to the principles of Islamic economics that benefit all people